Does local public investment boost enterprise performance? Evidence from Vietnam - Sy, Cuong Vu; Huyen, Trang Luu (Asian Development Policy Review, 2025)
This paper seeks to deepen our understanding of how local public investment and the quality of insititution impact enterprise performance in developing countries. The theoretical model presents two contrasting effects of public investment on enterprises. On the one hand, public investment can boost the marginal productivity of private capital. On the other hand, limited access to financing might crowd out private businesses. This study looks at enterprise survey data from 2011 to 2020 along with time series and cross-sectional data using a FEM (fixed effects model) across 63 provinces in Vietnam. The results show that the crowding-in effect is the most important. This effect is especially strong in provinces with robust institutions. The study underscores the crucial roles of local investment and institutional quality in enhancing business performance. Furthermore, macro factors like economic growth, inflation, and urbanization influence enterprise performance. The study also found that the number of employees has a positive impact on enterprise performance, while the age of the enterprise and its fixed assets have the opposite effect. To stimulate business growth, it is essential to sustain increases in local public investment, with a focus on infrastructure. The research findings highlight the importance of further enhancing the institutional environment.